Not of an age but for all time: Shakespeare’s Juliet before and after - Bartolamei, Rafaela Lomba (2022)
This dissertation focuses on the character of Juliet from Romeo and Juliet (1595) by William Shakespeare (1564-1616), focusing on its sources and various retellings and adaptations since the sixteenth century until the twenty-first. Discussing Juliet’s relationship with language, the body, love and marriage, and death, I examine the changes this character has suffered through the centuries in her many representations, especially investigating contexts in which she was tamed, i.e., robbed of her power and intelligence. To ponder on questions of adaptation and appropriation, I resort to Linda Hutcheon (2006) and Julie Sanders (2006) and I work with a variety of media in which Juliet is featured: cinema, ballet, song, comic books, and plays.